Estimated of metal mineral distribution using Induced Polarization (IP) Geolistric in Malalak West Sumatra Indonesia - Ahmad Kasasi; - Akmam (PILLAR OF PHYSICS, 2020)
The Malalak area in West Sumatra Indonesia area located around the volcano and generally rich in economically valuable metal minerals,  however, the presence of minerals in nature is not easy to find. The existence of economically valuable minerals around volcanoes, such as Mount Singgalang has not been widely revealed. Based on the above, a study aimed to estimate the distribution of metal minerals in Malalak Subdistrict, Agam Regency when viewed by the Geoelectric Induced Polarization (IP) method was conducted. Research is needed as reference data to predict mineral potential in the study area so that it can be used by the Malalak community. The exploration method used in this research is the Geoelectric Induced Polarization (IP) method. Data obtained by measuring using the ARES measuring instrument. Data processing uses Res2Dinv software to obtain 2D cross-sections and the data is interpreted using Smoothness-Constraint Least-Square inversion. Based on the estimates made to determine the distribution of minerals in the Malalak District, the types of minerals are Bornite in Line 1 with Chargeability of 6.93 msec and mineral Galena in Line 2 with Chargeability of 4.30 msec. The rock types found in Malalak District, consist of Sandstone, Limestone, and Granite. Track 1 has a type of rock with a resistivity value, namely Sandstone with a value of 58.4 Ωm - 295 Ωm, Limestone with a value of 296 Ωm - 1,501 Ωm and Granite with a value of 1,502 Ωm - 38,768.04 Ωm. Track 2 has a rock type with a resistivity value, namely Sandstone with a value of 58.5 Ωm - 287 Ωm, Limestone with a value of 288 Ωm - 1,412 Ωm and Granite with a value of 1,413 Ωm - 34,179.12 Ωm.